The Use of Problem Based Learning to Improve Students’ Critical Thinking in Indonesian Junior High School - Oktaviani, Helda; Suharsih, Siti; Handayani, Rita (Journal of Linguistics, Literacy, and Pedagogy, 2024)
Problem-based learning (PBL) is an instructional method in which students learn through facilitated problem solving. In PBL, students work in collaborative groups to identify what they need to learn to solve a problem. They engage in self-directed learning and then apply their new knowledge to the problem and reflect on what they learned and the effectiveness of the strategies used. The teacher acts to facilitate the learning process rather than impart knowledge. The goal of PBL is to help students develop 1) flexible knowledge, 2) effective problem-solving skills, 3) effective collaboration skills. This article aims to find out whether PBL can help students to think critically and how teachers implement Problem Based Learning in English class. In addition, this research was conducted in class VIII D with 30 students, there are 15 females and 15 males of SMPN 21 Kota Serang using qualitative case study method. The data was collected used observation and interview. The result of this study shows that Problem Based Learning helps students to think critically.